2x+27=6x+3

Simple and best practice solution for 2x+27=6x+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2x+27=6x+3 equation:


Simplifying
2x + 27 = 6x + 3

Reorder the terms:
27 + 2x = 6x + 3

Reorder the terms:
27 + 2x = 3 + 6x

Solving
27 + 2x = 3 + 6x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-6x' to each side of the equation.
27 + 2x + -6x = 3 + 6x + -6x

Combine like terms: 2x + -6x = -4x
27 + -4x = 3 + 6x + -6x

Combine like terms: 6x + -6x = 0
27 + -4x = 3 + 0
27 + -4x = 3

Add '-27' to each side of the equation.
27 + -27 + -4x = 3 + -27

Combine like terms: 27 + -27 = 0
0 + -4x = 3 + -27
-4x = 3 + -27

Combine like terms: 3 + -27 = -24
-4x = -24

Divide each side by '-4'.
x = 6

Simplifying
x = 6

See similar equations:

| .5x+3y=2 | | .67=ln(y) | | h=16t^2+vt+s | | 12+(5-9)= | | 3.2d=15.75+54.15 | | 7-x=7x+39 | | 6x+2x-9=95 | | -5x-2=x-2 | | 20x+35x=121 | | 5-2(x+2)=13 | | 14x-3+30=16x+11 | | x/3*4=20 | | 95=8x-8 | | 5+2(3x-8)=2x+9 | | 11+d+(-4)ford=-6 | | k^2-32k+8=0 | | 3(8.2-x)=6.6 | | -2(3x-2)=4-6x | | 26=6(5-a)+2 | | 7*5=63-N | | x/34=20 | | 56=t-25 | | 12x+11+69=25x+2 | | -5x-4=-3x+10 | | -10p-8=2 | | 3x+10y=-4 | | 63x^3+108x^2+81x= | | 2u-3=3 | | 6x+7=-2+7x | | 7x^2+12x+9= | | 7x-4(x+5)=16 | | x-10=-38+5x |

Equations solver categories